Impact of Diglossia on Word and Non-word Repetition among Language Impaired and Typically Developing Arabic Native Speaking Children - Saiegh-Haddad, Elinor; Ghawi-Dakwar, Ola (Frontiers in Psychology, 2017)
The study tested the impact of the phonological and lexical distance between a dialect of Palestinian Arabic spoken in the north of Israel (SpA) and Modern Standard Arabic (StA or MSA) on word and non-word repetition in children with specific language impairment (SLI) and in typically developing (TD) age-matched controls. Fifty kindergarten children (25 SLI, 25 TD; mean age 5;5) and fifty first grade children (25 SLI, 25 TD; mean age 6:11) were tested with a repetition task for 1–4 syllable long real words and pseudo words; Items varied systematically in whether each encoded a novel StA phoneme or not, namely a phoneme that is only used in StA but not in the spoken dialect targeted. Real words also varied in whether they were lexically novel, meaning whether the word is used only in StA, but not in SpA. SLI children were found to significantly underperform TD children on all repetition tasks indicating a general phonological memory deficit. More interesting for the current investigation is the observed strong and consistent effect of phonological novelty on word and non-word repetition in SLI and TD children, with a stronger effect observed in SLI. In contrast with phonological novelty, the effect of lexical novelty on word repetition was limited and it did not interact with group. The results are argued to reflect the role of linguistic distance in phonological memory for novel linguistic units in Arabic SLI and, hence, to support a specific Linguistic Distance Hypothesis of SLI in a diglossic setting. The implications of the findings for assessment, diagnosis and intervention with Arabic speaking children with SLI are discussed.